New technologies - Holmes, Eduardo (Revista Universidad de Guayaquil, 2009)
The telecommunications industry does not stop; its development is progressing at such a rapid pace that it is almost impossible to accurately review it in any book, much less in an article, because by the time it is published, changes will have already occurred and everything written loses relevance.When we say Communication Technology, we are referring to the equipment, organizational structure, and social values through which individuals gather, process, and exchange information with other individuals (E.M. Rogers).